Divergent Solid‐Phase Synthesis and Biological Evaluation of Yaku'amide B and Its Seven E/Z Isomers. Issue 3 (16th December 2020) - Kamiya, Koichi; Miura, Kensuke; Itoh, Hiroaki; Inoue, Masayuki
Abstract: Yaku′amide B (1 ) inhibits cancer cell growth through a unique mechanism of action. Compound 1 binds to mitochondrial Fo F1 ‐ATP synthase, inhibits ATP production, and enhances ATP hydrolysis. The presence of one ( E )‐ and two ( Z )‐α, β‐dehydroisoleucines (ΔIle) in the linear 13‐mer sequence is the most unusual structural feature of 1 . To uncover the biological importance of these residues, we synthesized 1 and its seven E / Z isomers 2 –8 by devising a new divergent solid‐phase strategy. Both the ( E )‐ and ( Z )‐ΔIle residues were stereoselectively constructed by traceless Staudinger ligation on resin to ultimately deliver 1 –8 . All isomers 2 –8 displayed effects on the inhibition of cell growth and ATP production, and enhanced ATP hydrolysis, thus indicating that 2 –8 share the same mode of action as 1 . The least potent isomer, 8, was isomeric at three ΔIle residues of the most potent 1 . These findings together indicate that the E / Z stereochemistry of the three ΔIle residues controls the magnitude of the biological functions of 1 . Abstract : The importance of ΔIle : Yaku′amide B (1 ) displays potent antiproliferative activity against cancer cells and possesses unusual ( E )‐ and ( Z )‐α, β‐dehydroisoleucines (ΔIle) in its linear 13‐mer sequence. We stereoselectively constructed 1 and its seven ( E )/( Z )‐ΔIle isomers 2 –8 by devising a new divergent solid‐phase strategy and revealed that the E / Z stereochemistry affects the biological activities.